ANALYSIS OF LOCAL TAX INCENTIVE POLICY IN ATTRACTING INVESTMENT AND CREATING LOCAL JOBS - Loso Judijanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to analyse the effectiveness of local tax incentive policies in attracting investment and creating local jobs. The method used is a literature study by reviewing various literatures, laws and regulations, official reports, and previous research results related to local tax incentives in Indonesia. The results of the analysis show that local tax incentives, such as tax reduction, exemption, and postponement of tax payments, contribute positively to increased investment and expansion of employment opportunities at the local level. However, the effectiveness of these policies is highly influenced by the regulatory design, institutional capacity, and ease of administrative procedures applied in each region. Challenges faced include regulatory complexity, limited supervisory capacity, and the need for policy harmonisation between central and local governments. This study recommends the need for periodic evaluation, simplification of procedures, and strengthening coordination between stakeholders so that local tax incentives can have an optimal and sustainable impact on economic growth and the welfare of local communities.